Artificial Recharge of an Unconfined Aquifer Using Treated Wastewater as a Climate Change Mitigation Strategy - Mukheef, Rana A. H.; Hassan, Waqed H.; Alquzweeni, S. (Civil Engineering Journal, 2024)
Worldwide groundwater extraction has increased dramatically during the past six decades. Water scarcity will affect 1.4 billion people in around 48 nations by 2025. Iraq is experiencing an unparalleled and severe water crisis due to various factors, including climate changes, insufficient rainfall, the policies of neighboring nations, and the increased demand resulting from population expansion. The research area (Dibdiba aquifer) is in Iraq, in the middle between Najaf and Karbala. It was observed that farmers had abandoned numerous wells as a result of the decline in their water levels. Groundwater is the water resource for the region, and due to high agricultural and industrial demand, the Dibdiba aquifer is facing groundwater depletion. This study utilized climatic datasets projected under two scenarios obtained from CMIP6 and the Groundwater Modeling System (GMS). The objective was to evaluate the effect of projected climate change on the quantity of groundwater. Artificial recharge of treated wastewater from the wastewater treatment plant (WWTP) in Kerbala into groundwater aquifers has proven to be an effective method of mitigating groundwater depletion while providing a sustainable water supply. Eleven wells are distributed randomly within the research area; each of them is located within the unconfined aquifer. The groundwater levels in these wells were measured in situ from July 2023 to April 2024. The model was run for steady and unsteady flow conditions, and calibration at steady state was carried out using the groundwater head data for (7) wells. These seven wells were selected to represent the whole research region as well as shorten the simulation run duration in the calibration process. On the other hand, the transient calibration was performed employing measurements of groundwater heads for four wells. Calibration and validation results indicated convergence between the observed and simulated heads. The modeling findings showed that the increment in groundwater level is about 1.0, 1.85, and 2.25 m with artificial recharge of about 6000 m³/day, 9000 m³/day, and 12000 m³/day, respectively. The above findings illustrate the ability of artificial recharge as a highly promising strategy for addressing the water depletion and environmental issues in the Dibdiba aquifer. Doi: 10.28991/CEJ-SP2024-010-016 Full Text: PDF